The Independence of São Tomé e Príncipe and Agrarian Reform - Eyzaguirre, Pablo B. (Cambridge University Press, 1989)
The Democratic Republic of São Tomé e Príncipe is the smallest country in lusophone Africa. The inhabitants of these two islands in the Gulf of Guinea just north of the Equator number approximately 115,000 of whom over 95 per cent live on São Tomé which has a total area of 857 sq. km. The smaller island of Príncipe, with only 140 sq. km, is inhabited primarily by Cape Verdeans whose ancestors migrated there during the colonial era. The economy has always been dominated by cocoa plantations, known as roças, which despite changes in organisation have been the fundamental sociopolitical foundation of this creole African society. The continuity of this unit of production in the national economy, and its attendant impact on the structure of society, remains the central problem facing the country's leaders.